Equity in Two Person Situations: Some Consequences - Hammond, Peter J. (Econometrica, 1979)
[Suppose that social choice is based on interpersonal comparisons of welfare levels. Suppose too that, whenever all but two persons are indifferent between two options, a choice is made between these options which is equitable, in some sense. Then provided that individual welfare functions are unrestricted, and social choice is independent of irrelevant alternatives, it follows that social choice is always equitable, in the same sense. This applies when equity means satisfying Suppes' indifference rule, or Suppes' original justice criterion, or the lexicographic extension of Rawls' difference principle.]